Enhancing Construction Project Success Through Proactive Risk Management in Yemen: A Quantitative Analysis - Al-Kateb, Fares Mohammed Abdulrahman; Arviansyah (AFEBI Management and Business Review, 2024)
This study applied quantitative analysis to investigate the relationship between risk management performance and construction project success in Yemen. The study utilized statistical tools such as SmartPLS software to assess the influence of good risk management methods on project results. The study's focus on proactive risk identification, analysis, reaction, and monitoring and control seeks to improve risk management performance and assure project success. To examine the variables, Structural Equation Modeling (SEM) was used with SmartPLS version 3 and data from 171 respondents ranging from low to high management levels. The study presents empirical evidence for the beneficial effects of strong risk management methods on project success and the structural model. The findings highlight the strong link between risk management and project outcomes, emphasizing the necessity of early risk identification, analysis, reaction, and monitoring and control. Based on the quantitative analysis results, practitioners are given recommendations on how to prioritize successful risk management techniques. This study advances the knowledge of risk management in construction projects and gives practical insights for improving project outcomes through data-driven decision-making.